Analisis Prosedur Revisi Daftar Isian Pelaksanaan Anggaran Satuan Kerja Kepada Kantor Wilayah Direktorat Jenderal Perbendaharaan Provinsi Jawa Barat - Totoh Abdulfatah; Runita Arum Kanti (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
Budgets are important for the sustainability of a country. Budgets are used for economic policy and also finance government activities. When the economy is down and the private sector is not functioning well, government spending can help boost the economy. Government expenditure is contained in the State Budget (APBN). Good budget absorption must be accompanied by good budget planning. Budget absorption can be used as an indicator to show the effectiveness of programs that have been carried out by the government. budget revision is a change in the details of the budget made based on the APBN in one fiscal year and has been approved in DIPA per fiscal year. the methods used are literature study, observation and interviews with staff in the field of Budget Implementation Development 1 (PPA-1) and the Head of the Budget Implementation Development Section 1 (PPA-1). Based on the results of interviews conducted with the Head of Section PPA 1C explained that budget revisions can occur due to several factors including changes in government policy, contractual and self-management budget leftovers without reducing planned outputs and there have also been a number of problems, including the use of priority budgets, operational cost deficits, changes in government policy, and unclear priorities for the budget implementation period.